(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses a set of engineering design measures, as well as an analysis of the three main methods of seismic protection, increased seismic resistance of load-bearing and enclosing structures of buildings and structures.